Effect of austempering temperature on microstructure of ausferrite in austempered ductile iron. Issue 11 (24th July 2019) - Wang, Chengduo; Liu, Ruizhuo; Li, Songjie; Gu, Chang; Du, Xueshan; Sun, Yufu; Tian, Junfeng
ABSTRACT: The effect of austempering temperature on the microstructure of ausferrite in austempered ductile iron was investigated. The results show that the grain sizes of retained austenite and acicular bainitic ferrite both become larger with the increase of austempering temperature. As the austempering temperature is 240°C, the crystallographic relationship between ferrite and austenite in ausferrite follows Greninger-Troiano relation. However, Nishiyama–Wassermann relation and Greninger-Troiano relation both appear in ausferrite austempered at 300°C. At this temperature, the point-to-point misorientations of individual ferrite needle austempered at 300°C are less than 1°, being less than those at 240°C. This means the ferrite needles at 300°C contain fewer defects. However, some poles of ferrite needles obviously deviate from their ideal positions, which mainly comes from some ends of ferrite needles.